Knowledge, attitude, practice, and pattern of substance use among adolescents and young adults from Aligarh, India - Faizi, Nafis; Alvi, Yasir; Saraswat, Ambika; Yasir, Mohd. (Indian Journal of Community Health, 2021)
Background: Substance use disorders are significant public health problem among adolescents and young adults. Aim & Objective: We did this study to observe knowledge, attitude, and practice of substance use among school and college going adolescents and young adults. Material & Methods: A cross-sectional study was conducted at 10 schools and colleges from Aligarh. A total of 1431 students were approached with study tools comprising of pre-structured proforma on knowledge, attitude, and practice. Results: We observed that most of the students (89%) had some knowledge about substance use. The risk-taking attitude was common even against drugs like cocaine and charas (30.6% and 29.1% respectively). A high prevalence of ever user and current user was observed (33.3% and 12.9% respectively). The mean age of starting the drug in students and their friends was 15.5 ±2.7 and 16.2 ±2.8 years respectively. Among the ever users, tobacco smoking (56.6) and alcohol (47.6%) were most common. Stress (57.9%) was most common reason to use drugs. Males and college students (40.6% and 41.2% respectively) were using it more. Conclusion: This study found half-baked knowledge, propensity towards a risk-taking attitude, and a substantial prevalence of substance use practices. Proper action and further researches are required to explore variables associated for reducing the prevalence.